Síndrome diarreico en potrillos, diagnóstico y caracterización de los agentes virales involucrados - Miño, Orlando Samuel (2017)
Neonatal diarrhea is one of the most relevant and frequent syndromes in foals younger than six month of age. Group A Rotavirus (RVA) is the main viral agent associated to diarrhea in foals, worldwide. However, around 50% of the diarrhea episodes remain without an etiological diagnosis. The aims of the present work were, to go in detail into the molecular epidemiology, the evolutive and structural characteristics of equine RVA and to investigate the presence and role of other viral agents as potential causes of diarrhea in Argentinean foals. The study in equine RVA started with the evaluation of the sensitivity and specificity of tree diagnosis tests. Secondly, we studied the molecular epidemiology of the RVA circulating in Argentinean foals from 2009 to 2014. The G3P[12] and G14P[12] genotypes were detected with a cyclic prevalence among the years under study. Considering all the genome sequences of the equine RVA strains available an evolutive study allowed us to determine the monophyletic clustering of the equine RVA detected in Argentina. The E12 genotype -encoding the viral enterotoxin NSP4- was defined as a geographical marker which allows describing the evolution of the equine RVA present in South America since the first foundation of Buenos Aires in 1536. The obtained results led to the hypothesis that an inter-species transmission gave rise to new RVA genome constellations as a result of gene reassortment between the RVA circulating in American autochthonous species (Lama guanicoe) and the RVA of the introduced species (equine and bovine). The E12 gene from the autochthonous RVA to the equine and bovine RVA backbones were transferred and fixed. The study of equine RVA also included a structural analysis that showed the genetic linkage between the two genotypes of the VP7 and VP6 structural proteins. Finally, the virome of diarrheic samples from foals were studied by ?next generation sequencing? technology. In conclusion the present work contributed new information regarding equine RVA diagnosis and addressed aspects related to evolutive, phylodynamic and structural processes of RVA that might be extrapolated to other viruses carrying segmented genomes. In addition, the analysis of the virome from samples from diarrheic foals allowed us to detect other potential viral agents associated to diarrhea in equines. Our results remark the important of conducting the continuous surveillance of diarrhea in foals, the identification and characterization of the associated viral agents with the final goal of the rationale design of new control and preventive tools.